1997
DOI: 10.1002/(sici)1097-0142(19970715)80:2<198::aid-cncr5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Thallium-201 single photon emission computed tomography as an indicator of prognosis for patients with lung carcinoma

Abstract: The authors calculated the uptake ratio to evaluate the degree of Tl-201 uptake in the primary tumor. This ratio was compared with survival time and other prognos-1 Department of Respiratory Medicine, Nikko tic factors. Memorial Hospital, Muroran, Japan. RESULTS.The authors studied 152 patients (125 men and 27 women). The group 2 Department of Nuclear Medicine, School of of patients with the low Tl-201 uptake ratio survived longer than the group of Medicine, Hokkaido University, Sapporo, Japan.patients with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…The authors in fact believe it to be a non-invasive marker in predicting the prognosis in carcinoma lung cases. 27 Our study has also demonstrated that higher the grade of tumour higher is the 201 Tl uptake. Quantifying the 201 Tl uptake hence is extremely useful in diagnosis as well as knowing the differentiation level of the tumour.…”
Section: Discussionsupporting
confidence: 58%
“…The authors in fact believe it to be a non-invasive marker in predicting the prognosis in carcinoma lung cases. 27 Our study has also demonstrated that higher the grade of tumour higher is the 201 Tl uptake. Quantifying the 201 Tl uptake hence is extremely useful in diagnosis as well as knowing the differentiation level of the tumour.…”
Section: Discussionsupporting
confidence: 58%
“…18,19 Therefore, it may be expected that 201 Tl would be useful in predicting the therapeutic response and prognosis of patients with this type of tumor. 20,21 In the current study, we evaluated whether a therapeutic response in patients with lung carcinoma is predictable by dual-isotope single photon emission computed tomography (SPECT) with 99m Tc-TF and 201 Tl. We employed a dual-isotope SPECT, which is well established in the field of nuclear medicine.…”
Section: Resultsmentioning
confidence: 99%
“…While a higher uptake correlates with a worse prognosis in lung cancer and sensitivity better for poorly differentiated lung cancers, 10 11 thallium is more sensitive in low -grade lymphomas, 10 11 though it may be even more so in intermediate-grade lymphomas. 12 As thallium tumor studies were usually minutes to hours after injection rather than immediately after injection for 82 Rb, 10 11 12 13 14 the physiology may be very different in any case. Nonetheless, despite the inconsistent correlation of thallium with tumor differentiation, the possibility of a correlation of Rb with ER activity bears further study.…”
Section: Discussionmentioning
confidence: 99%